ANALISIS BERPIKIR KRITIS SISWA DALAM PEMECAHAN MASALAH MATEMATIKA BERDASARKAN POLYA PADA POKOK BAHASAN PERSAMAAN KUADRAT (Penelitian pada Siswa Kelas X SMK Muhammadiyah 1 Sragen Tahun Pelajaran 2013/2014) - Harlinda Fatmawati; Mardiyana Mardiyana; Triyanto Triyanto (Jurnal Pembelajaran Matematika, 2014)
Abstract : This research aims were to describe: (1) students’ level of critical thinking, (2) students’ process of critical thinking in problem solving based on Polya, (3) factors influencing students’ process of critical thinking. This was a descriptive qualitative research. Subject of the research was students grade X AP 1 of SMK Muhammadiyah 1 Sragen consisting of four students. Subject was selected using purposive sampling. Instrument of collecting data were observation, problem solving test and interview. Validity of the data was tested using triangulation method. The data were analyzed by: (1) classifying the data in level of critical thinking based on indicators of critical thinking stated by Ennis; (2) analyzing each critical thinking level based on four steps of Polya’s problem solving; (3) analyzing factors influencing students’ process of critical thinking. From the research on 36 students, the results of students’ level of critical thinking are 19.4% for critical thinking level 0, 72.2% for critical thinking level 1, 5.6% for critical thinking level 2 and 2.8% for critical thinking level 3. Students’ process of critical thinking in (a) understanding problems, critical thinking level 0 was not able to construct point of the problems and reveal the facts, critical thinking level 1, 2, and 3 were able to construct point of the problems and reveal the facts; (b) making a plan, critical thinking level 0 was not able to detect the bias and determine theorem in solving problems, critical thinking level 1 was not able to detect the bias but was able to theorem in solving problems, critical thinking level 2 and 3 were able to detect the bias and determine theorem in solving problems; (c) carrying out the plan, critical thinking level 0 was not able to solve problems as the planning, critical thinking level 1, 2 and 3 were able to solve problems as the planning; (d) looking back the completed solution, critical thinking level 0 and 1 were not able to select logical argument and to draw conclusion, however, critical thinking level 1 was able to solve the problems using another method, critical thinking level 2 was not quite able to select logical argument and to draw conclusion, but it was able to solve the problems using another method, and critical thinking level 3 was able to select logical argument, to draw conclusion and to solve the problems using another method. Factors influencing students’ process of critical thinking are students were not accustomed to solve story problems so that they were not able to understand the problems, students found it difficult to construct Mathematics model, and students were accustomed to solve questions using only one method.Key words: Critical thinking, Polya’s problem solving, Process of critical thinking, Level of critical thinking.